Related party transaction disclosure: compliance, determinants, value-relevance and real earnings management - Maigoshi, Zaharaddeen Salisu (2018)
Expropriation through Related Party Transaction (RPT) has been identified as one of the key factors that led to the collapse of several firms globally. Hence, its regulation becomes necessary. This study examines the extent and the determinants of compliance with the disclosure requirements on RPTs by Malaysian listed firms. It also investigates the value-relevance of Malaysian Financial Reporting Standard (MFRS) 124 adoption, real earnings management (REM) in RPTs and the moderating effect of compliance with MFRS 124 on the relationship between REM in RPTs and firm value. The study uses the data collected from the firms with significant RPTs from 2009 to 2015. Findings from the weighted disclosure index indicate a moderate level of compliance with MFRS 124. Furthermore, the regression results reveal that board independence, audit committee financial expertise, family ownership, managerial ownership and firm growth have significant positive relationships with the compliance of MFRS 124. Moreover, the study documents that RPTs disclosure is value-relevant. Findings of price model provide evidence that with the adoption of MFRS 124, capital market participants value the EPS of the RPT firms over its BVPS. The study documents that firms use RPTs to perpetrate REM. The results of the Roychowdhury models show that RPTs firms are characterized by low cash flow from operations, high production costs and low discretionary expenditures. It is also established that capital market discounts the stock price of firms that perpetrate REM in RPTs. Also, compliance with disclosure requirements on RPTs mitigates the negative relationship between REM in RPTs and firm value. The study reveals the need for the relevant authorities to increase the level of enforcement to achieve full compliance which will result to increase transparency of financial reporting and investor protection. The results of this study contribute to the agency, resource dependency and capital market theories.